2021
DOI: 10.1016/s1473-3099(20)30559-4
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to vaccinate against COVID-19 in Australia

Abstract: asymptomatic, presymptomatic, or even oligosymptomatic, has also been well established, 6,7 despite claims to the contrary by Abbas and Pittet. With high viral titres in the oral fluid of such carriers well documented and a substantial proportion of speech droplets of oral fluid now shown to remain airborne for many minutes, inhalation of such particles represents a direct route to the nasopharynx. Retrospective analyses of indoor superspreader events further support the role of speech droplets in airborne tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

43
276
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(328 citation statements)
references
References 4 publications
43
276
9
Order By: Relevance
“…The difference in acceptance rate documented in this study may be due to a single or combination of factor(s) including: (1) the variation in the wording of the question; (2) high level of confidence and trust in the Australian government [6] or (3) due to concerns about increasing local transmission which were high at the time. However, our results align with other Australian studies, which have reported willingness levels between 76% to 86% [13,14]. Both studies collected the data in April 2020.…”
Section: Discussionsupporting
confidence: 91%
“…The difference in acceptance rate documented in this study may be due to a single or combination of factor(s) including: (1) the variation in the wording of the question; (2) high level of confidence and trust in the Australian government [6] or (3) due to concerns about increasing local transmission which were high at the time. However, our results align with other Australian studies, which have reported willingness levels between 76% to 86% [13,14]. Both studies collected the data in April 2020.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the present study, other studies appearing after our study had been completed have found that vaccination hesitancy is associated with negative attitudes toward a SARSCoV2 vaccine, including concerns about safety and efficacy (Fisher et al, 2020;Neumann-Böhme et al, 2020;Palamenghi et al, 2020), and doubts about the necessity for vaccination (Dodd et al, 2020). Findings from the present study, along with results from previous studies, have important implications for public policy.…”
Section: Discussionsupporting
confidence: 90%
“…The degree of vaccination hesitancy found in the present study is broadly consistent with other studies that were published after our study had been completed. Studies conducted during March-April 2020, which was somewhat earlier than the present study (May, 2020), reported findings broadly similar to ours in terms of percentages of people who stated that they would not get vaccinated against SARS-CoV2: Italy (14%) (Barello et al, 2020), France (26%) (COCONEL Group, 2020), and Australia (14%) (Dodd et al, 2020). In a European survey in June, 2020, 24% of respondents stated that they were either unwilling or unsure about getting vaccinated (Neumann-Böhme et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…However, the success of any vaccination programme depends on high vaccine acceptance and uptake. Previously, Rachael Dodd and colleagues 1 reported that 4·9% of adults in Australia would refuse a vaccine, which is low compared with estimates in the USA (20%) 2 and France (27%). 3 The Australian data were collected in April, 2020, 4 weeks after lockdown measures commenced, which was at a time when community transmission was perceived to be high.…”
mentioning
confidence: 95%